Confusion of Legal Roots: Comparative Historical Review of International Trade Law in France and Indonesia - Aurele Magnan; Kevin John Paul Manurung; Dao Gia Phuc; Rahmi Ayunda (Journal of Judicial Review, 2021)
This research discusses the history of international trade law in France and Indonesia. This research is a doctrinal research that uses normative legal research methods. The data used are data obtained indirectly, such as legislation, previous research and other secondary data relevant to the main object of the article, and several cases of the World Trade Organization. The Oxford Journal has defined the term 'International Trade' as the involvement of goods and/or services across national boundaries. In other words, it was an expansive movement. Such actions have been going on for centuries. Thanks to the lex mercatoria and lex maritime created in the Middle Ages, also to the important role of the 'silk road' which ironically connected the road between France and Indonesia, because it provided so many benefits and the development of international trade law. . After all, French regulations inspired so many rules in many countries, including the Netherlands and were applied in Indonesia as a colony. Indonesia had some similiarities within France ever since so.